Republic of Haiti Education Management Information Systems : SABER Country Report 2017 - Abdul-Hamid, Husein; Mayrhofer, Diana; Saraogi, Namrata (World Bank, Washington, DC, 2018)
The main objective of this paper is to outline what matters most for an effective education management information system (EMIS). It presents the conceptual background and operational tools for the Systems Approach for Better Education Results (SABER)‐EMIS domain. These tools are intended for use by government education policy makers to assess policy areas of relevance to a country’s EMIS against international best practices. This paper begins with an introduction of the domain and the rationale for an EMIS benchmarking tool. Chapter one then provides an overview of current data‐related demands to improve education, explains how an EMIS meets those data demands, and highlights examples of specific systems in action. Chapter two outlines what matters in an EMIS, starting with an explanation of what comprises the construct validity and theoretical underpinnings for benchmarking an EMIS. This chapter shows that the guiding principles behind an EMIS drive actionable policies. A detailed description of four policy areas, specifically, the enabling environment, system soundness, data quality, and utilization for decision making, then follows in chapter three. That chapter describes the rubric for the SABER‐EMIS Tool and gives a brief overview of an EMIS benchmarking pilot, which demonstrated the feasibility of the concept. The last chapter describes how an EMIS is benchmarked, scored, and subsequently leads to a situation analysis. This assessment sequence provides an understanding of the strengths and weaknesses of an EMIS system for a fuller, more comprehensive depiction of its status. Overall, this paper evaluates whether a management information system is set up to use the information it generates for improving operational efficiency and educational quality.